2021
DOI: 10.3390/fractalfract5030119
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in Thermal Energy and Solute Particles Using Hybrid Nanoparticles by Engaging Activation Energy and Chemical Reaction over a Parabolic Surface via Finite Element Approach

Abstract: Several mechanisms in industrial use have significant applications in thermal transportation. The inclusion of hybrid nanoparticles in different mixtures has been studied extensively by researchers due to their wide applications. This report discusses the flow of Powell–Eyring fluid mixed with hybrid nanoparticles over a melting parabolic stretched surface. Flow rheology expressions have been derived under boundary layer theory. Afterwards, similarity transformation has been applied to convert PDEs into associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 459 publications
(62 citation statements)
references
References 19 publications
(18 reference statements)
0
62
0
Order By: Relevance
“…For example, through Lorentz forces, the control of a stream might be recognized. Recently, a few research articles have managed the limit layer stream issue by extending the surface in the navigated stream under the effect of the magnetic fields [1][2][3][4][5][6][7][8]. These investigations of fluid over an extending sheet are a basic problem in various applications in mechanical fields, for example, polymer sheets and the strand ejection of polymers to the wind-up roller, for which a faraway limited separation is then arranged.…”
Section: Introductionmentioning
confidence: 99%
“…For example, through Lorentz forces, the control of a stream might be recognized. Recently, a few research articles have managed the limit layer stream issue by extending the surface in the navigated stream under the effect of the magnetic fields [1][2][3][4][5][6][7][8]. These investigations of fluid over an extending sheet are a basic problem in various applications in mechanical fields, for example, polymer sheets and the strand ejection of polymers to the wind-up roller, for which a faraway limited separation is then arranged.…”
Section: Introductionmentioning
confidence: 99%
“…The concept upon which the finite element method rests is the division of the required domain into elements (finite). FES (finite element scheme) [8,17] is discussed here. The flow chart of the finite element algorithm is mentioned in Figure 3.…”
Section: Numerical Schemementioning
confidence: 99%
“…They monitored the decline in fluid temperature against the Prandtl number and the concentration was controlled for the higher values of the Schmidt number. Chu et al [8] examined the involvement of chemical reaction and activation energy in the nanofluid flow problem. They solved the resulting equations numerically via a finite element procedure, recording the decline in the fluid velocity against the magnetic parameter.…”
Section: Introductionmentioning
confidence: 99%
“…In their investigation, which was based on experimental results, a relationship had been proposed to calculate the heat transfer coefficient of helical inner tubes. In another study, Jayakumar et al (2010) numerically studied (Chu et al, 2021) single-phase currents within helical tubes. The results of their study showed changes in the local Nusselt number (Nu) along the length and circumference of the wall of a helical tube.…”
Section: Introductionmentioning
confidence: 99%